Implementing psychosocial programming at a level 1 trauma center: results from a 5-year period. Issue 1 (21st January 2020) - Simske, Natasha M; Rivera, Trenton; Breslin, Mary A; Hendrickson, Sarah B; Simpson, Megen; Kalina, Mark; Ho, Vanessa P; Vallier, Heather A
Abstract : Background: The primary goal of the present study is to describe the psychosocial support services provided at our institution and the evolution of such programming through time. This study will also report the demographics and injury patterns of patients using available resources. Methods: Trauma Recovery Services (TRS) is a social and psychological support program that provides services and resources to patients and families admitted to our hospital. It includes a number of different services such as emotional coaching from licensed counselors, educational materials, peer mentorship from trauma survivors, monthly support groups, post-traumatic stress disorder (PTSD) screening and programming for victims of crime. Patients using services were prospectively recorded by hired staff, volunteers and students who engaged in distributing programming. Demographics and injury characteristics were retrospectively gathered from patient's medical records. Results: From May of 2013 through December 2018, a total of 4977 discrete patients used TRS at an urban level 1 trauma center. During the study period, 31.4% of the 15 640 admitted adult trauma patients were exposed to TRS and this increased from 7.2% in 2013 to 60.1% in 2018. During the period of 5.5 years, 3317 patients had 'direct contact' (coaching and/or educational materials) and 1827 patients had at least one peer visit. The average number of peer visits was 2.7 per patient (range: 2–15). Of the 114 patients who attended support groups over 4 years, 55 (48%) attended more than one session, with an average of 3.9 visits (range: 2–10) per patient. After the establishment of PTSD screening and Victims of Crime Advocacy and Recovery Program (VOCARP) services in 2017, a total of 482 patients were screened for PTSD and 974 patients used VOCARP resources during the period of 2 years, with substantial growth from 2017 to 2018. Conclusions: Hospital-provided resources aimed at educating patients, expanding support networks and bolstering resiliency were popular at our institution, with nearly 5000 discrete patients accessing services during a period of 5.5 years. Moving forward, greater investigation of program usage, development, and efficacy is necessary. Level of evidence: Level II therapeutic.